PENDEKATAN STUDI ORIENTALIS ATAS HADITS (Pemikiran Nabiaa Abbot Atas Hadits) - Rahma, Ainun; Al Ikra, Al Ikra; Fajrul, Moh.; Nurhalizah, Nurhalizah; Syaila, Vasqiah Siti; Mahendra, Yusril (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
This journal will discuss Nabiaa Abbot's thoughts on hadith, where we know that hadith is the second source of Islamic law after the Koran. And this is an important thing for not only Muslims to understand but also nonMuslims. Nabiaa Aboot is one of the pioneers of many women in the Islamic Middle East. Nabiia Aboot's thoughts on the hadith consist of three main parts, namely: a). Definition of Hadith or As-Sunnah, b). Hadith Codification, c). Criticism of Sanad and Matan. This article is a library research type. Using qualitative methods and a descriptive-analytic approach, this research confirms that Aboot tries to position hadith as something that cannot be separated from the Al-Qur'an, so an explanation from the Al-Qur'an is needed.